Ukraine's foreign and security policy, 1991-2000 - Wolczuk, Roman, 1962- (BASEES/RoutledgeCurzon series on Russian and East European studies ;, 2003)
This book analyses Ukraine's relations with each of its neighbours in the 1990s and the degree to which these relations fitted into Ukraine's broad objective of reorienting its key political ties from East to West.